2021
DOI: 10.1007/s00391-021-01926-3
|View full text |Cite
|
Sign up to set email alerts
|

Erfahrungen und Sichtweisen von Pflegeheimbewohnenden mit depressiver Symptomatik während der COVID-19-Pandemie: eine qualitative Studie

Abstract: Zusammenfassung Hintergrund Die COVID-19-Pandemie erfordert umfangreiche Maßnahmen in Pflegeheimen mit dem Ziel der Infektionsvermeidung. Diese Maßnahmen wirken sich auf das Leben der Bewohnenden aus und führen u. a. zu einer Zunahme an Depressivität und anderen negativen Begleiterscheinungen. Ziel der Arbeit Die Studie hat die Exploration der Erfahrungen und Sichtweisen von Pflegeheimbewohnenden mit depressiver Symptomatik während der Pandem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
5
0
4
Order By: Relevance
“…Importantly, studies analyzing data collected at different times during the pandemic showed that depressive symptoms fluctuated with a high prevalence after the onset of social isolation and a subsequent decrease when visiting restrictions were relaxed (Angevaare et al 2022 ; Górski et al 2022a , b ; Górski, Garbicz, et al, 2022 ; Levere et al 2021 ; Plangger et al 2022 ). Interviews with residents conducted during later phases of the pandemic confirm little psychological impact at that time (Schweighart et al 2021 ; Thomas et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, studies analyzing data collected at different times during the pandemic showed that depressive symptoms fluctuated with a high prevalence after the onset of social isolation and a subsequent decrease when visiting restrictions were relaxed (Angevaare et al 2022 ; Górski et al 2022a , b ; Górski, Garbicz, et al, 2022 ; Levere et al 2021 ; Plangger et al 2022 ). Interviews with residents conducted during later phases of the pandemic confirm little psychological impact at that time (Schweighart et al 2021 ; Thomas et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Estimates regarding cognitively impaired residents diverged, with Elderly Care Physicians (ECP) highlighting the difficulties these residents face when using video calls (Sizoo et al 2020 ), while proxies in two studies estimated the impact on the quality of life of cognitively impaired residents to be less severe (Paananen et al 2021 ; Wammes et al 2020 ). In December 2020, residents of a German LTCF found that visiting restrictions had little impact on their quality of life, while they complained about a lack of activities and boredom (Schweighart et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Deutlich wird allerdings auch, dass dieses Dilemma in vielerlei Hinsicht auch schon den vorpandemischen Alltag geprägt hat. Kontakteinschränkende Maßnahmen werden daher weitgehend unaufgeregt hingenommen [17,18]. Als große Belastung wird hingegen die Maßnahme der Zimmerquarantäne geschildert.…”
Section: Diskussionunclassified
“…Erste qualitative Studien zum Erleben der Pandemie weisen jedoch zunächst auf ein großes Ausmaß an Adaption und Akzeptanz durch die Pflegebedürftigen hin. Diese erleben zwar viele der Maßnahmen als Einschränkung [16,17], es lassen sich aber auch Mechanismen identifizieren, die auf eine hohe Resilienz schließen lassen [18].…”
Section: Introductionunclassified
“…In particular, people who indicated that they had lived their life and are ready to die reported no additional mental stress because of COVID-19 or the fear of a possible infection. Other respondents were more stressed by their concern for relatives, loneliness and generally increased anxiety [ 27 ]. In a survey by Wammes et al 2020, relatives of residents of Dutch nursing homes particularly reported increased loneliness (73%) and fear (26%) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%